The Effect of Cake Application Toward Students Speaking Mastery (A Quasi Experimental at the Tenth Grade Students of SMAN 04 Seluma Academic Year 2024-2025) - Elpita Sari; Ferri Susanto; Yashori Revola (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Research this study aimed to investigate the effect of 1using the Cake application on students’ English speaking ability at Grade X of SMA Negeri 04 Seluma in the academic year 2024/2025. Previous studies have reported that mobile-assisted language learning applications contribute positively to vocabulary mastery and listening skills; however, empirical evidence focusing specifically on speaking ability at the senior high school level, particularly in rural school contexts, remains limited. To address this gap, this research employed a quantitative approach using a quasi-experimental design involving two groups: an experimental group taught using the Cake application and a control group taught using conventional teaching methods. The research instrument was a speaking test consisting of 17 incomplete-sentence items administered at the pre-test and post-test stages. The instrument was tested and confirmed to be valid and reliable. The findings showed that the mean post-test score of the experimental group (74.79) was higher than that of the control group (62.23). Statistical analysis using a paired sample t-test indicated a significant difference between the two groups (0.000 < 0.05). These results indicate that the use of the Cake application is effective in improving students’ English speaking ability. Therefore, integrating mobile learning applications such as Cake can be considered a viable instructional strategy to enhance speaking skills in English language learning at the senior high school level.